Skirts, Stereotypes, and Silences: Representations of Women in Canadian Police Museums - Joshua, Courtney (Women & criminal justice, 2021)
Drawing from interviews, fieldnotes, and visual data, we examine representations of policewomen and gender communicated in Canadian police museums. We examine four trends from our dataset. First, we found silences regarding the history of women in policing in Canada. Second, there was a fetish-like emphasis on women’s police uniforms. Third, when included policewomen were treated in a tokenistic manner. By contrast, displays focusing on men treated them as policing heroes. We argue the history of policing may be one of white male domination, but this facet of social control should not be further normalized by erasing important elements of the histories of women from police museums. In the discussion, we explain what this analysis adds to literatures on representations of women in museums and on representations of policing.